Role of Environmental Ethics in the Conservation of Forests - Jolly Garg (International Journal of Pharma and Bio Sciences, 2020)
Above industrialization, excessive increase in human population, excessive consumerism and luxurious life-style are the some causes of depletion of natural resources including the forests? Elementary infrastructure of a particular ecosystem and is highly interlinked with people’s mind-set for ecology. Indian studies revealed that our ancient literature has a tremendous potential to enhance the values and ethics in terms of ecological knowledge. This study will provide new insights into the development of holistic background and that will help to identify those factors that restrict people to form a mindset for eco friendly. A broad review of literature reflects that alterations in once existing pattern of life and environment is inevitable in development. A revolutionary movement in terms of biodiversity conservation is at times relevant to alter this pattern in order to attain the objectives mentioned in CBD (Convention of Biodiversity). It is quite essential to gain a profound understanding of the environment and biodiversity conservation. Motivation and awareness about the negative impact of the dark side of the biodiversity loss has to be play an important role. During the course of development and rapid increase in human population, we are losing ethical values. Each and every individual is responsible for the depletion of ecosystem and the biodiversity; hence should carry on the responsibility to halt the erosion of biodiversity, conservation as well as eco-restoration. “Holistic Development” is essential and human beings have to follow the Global Ecosystem Approach. The “Environmental Ethics” can play a very significant and crucial role as ethics control the mind-set of an individual; so the environment, ecology and biodiversity. Environmental ethics also played significant role in the biodiversity conservation. We have to adopt the principle of three R’s i.e. Reduce, Recycle and Reuse of natural resources; rather than uncontrolled reproduction, luxurious use of natural resources, refusal to ecological unfriendly habits and re-adoption of ecological and eco friendly mindset. It is hard to tackle the psycho-socio-cultural barriers in biodiversity conservation. Efforts should be taken to attract, generate interest, clear doubts and inculcate the eco-friendly practices. It is very clear that “Environmental Ethics Development” initiatives be accorded in a daily routine of every human being.